Management of Genital Fistula in Women with Meyer-Rokitansky-Kuster-Hauser Syndrome - Jenner Lengmang, Sunday (Nepal Journal of Obstetrics and Gynaecology, 2018)
Aims: The study sought to document our experience with management of genital fistula and related symptoms in women with MRKH syndrome. Methods: This is a retrospective review of women with MRKH syndrome who were treated for genital fistula and related conditions from January 2012 to July 2018. Our Microsoft Access database and operation register were used to locate the folders from which data was extracted. Follow up information was obtained by telephone interview. Data was analysed with SPSS version 17. Results: The mean age at presentation of the six patients was 21.2 years (SD 4.5). Mean follow-up period was 27.3 months (SD 24.1). One patient presented with infertility; the remaining five presented with genital fistula (two iatrogenic, two gishiri cuts and one sexual trauma). Three fistulae were vesicovaginal and two rectovaginal. All fistulae were successfully repaired. All patients were offered sigmoid neo-vagina as one-stage or two-stage procedure for concerns about penetrative vaginal intercourse. To date, two patients are sexually active during follow-up, and have a pleasing and satisfactory penetrative neo-vaginal sexual experience. Conclusion: Women and girls with MRKH syndrome present with genital fistula from iatrogenic, harmful cultural practice and sexual trauma. Regardless of presenting complaints of women with MRKH syndrome, they also had concerns regarding penetrative vaginal intercourse. Depending on the mode of presentation, one- stage or two-stage surgical repair was possible and sigmoid neo-vaginal surgery provided a satisfactory penetrative neo-vaginal sexual outcome.